Improvement of the self‐assembly of low χ ABA triblock copolymers with the addition of an ionic liquid. Issue 3 (18th November 2022) - Guliyeva, Aynur; Pung, Hélène; Tencé‐Girault, Sylvie; Rébillat, Marc; Serghei, Anatoli; Gervais, Matthieu; Sollogoub, Cyrille; Roland, Sébastien
Abstract: Self‐assembly of high molecular weight commercially available low χ ABA triblock copolymers with ionic liquids (ILs) was observed after solvent casting without the implementation of an additional annealing step. Here, the addition of an IL to a triblock copolymer poly(methyl methacrylate‐ b ‐butyl acrylate‐ b ‐methyl methacrylate) (MAM) with an elastomeric central block and rigid end blocks is proposed to tune the self‐assembled morphology. Two different compositions of this copolymer with different initial microstructures (ill‐defined morphology without long‐range order and a lamellar morphology) were selected. The selectivity of the IL addition in one of the block phases was studied through the evolution of the glass transition of both blocks. The impact of the IL weight concentration on the morphology as well as the domain spacing is presented. Adding IL to the first copolymer detected a lyotropic disorder–order transition towards a gyroid morphology, observed even for a high molecular weight copolymer due to the low χ parameter, and for higher IL content a second transition to a lamellar morphology was observed. For the second copolymer, only an order–order transition (lamellae to cylinders) could be detected at high IL content. IL also enhanced the long‐range ordering of the MAM morphology obtained through solvent casting without additional annealing steps, compared with the same composition without IL. © 2022 Society of Industrial Chemistry. Abstract : The addition of ionic liquids to low χ ABA triblock copolymers improves the self‐assembly phenomenon after solvent casting without the implementation of an additional annealing step by mixing selectively into one of the blocks. Using these low χ block copolymers, high molecular weight gyroid morphology can be obtained.